Inside and Beyond Color: Comparative Overview of Functional Quality of Tomato and Watermelon Fruits - Ilahy, Riadh; Tlili, Imen; Siddiqui, Mohammed Wasim; Hdider, Chafik; Lenucci, Marcello Salvatore (Frontiers in Plant Science, 2019)
The quali-quantitative evaluation and the improvement of the levels of plant bioactive secondary metabolites are increasingly gaining consideration by growers, breeders and processors, particularly in those fruits and vegetables that, due to their supposed health promoting properties, are considered “functional.” Worldwide, tomato and watermelon are among the main grown and consumed crops and represent important sources not only of dietary lycopene but also of other health beneficial bioactives. Tomato and watermelon synthesize and store lycopene as their major ripe fruit carotenoid responsible of their typical red color at full maturity. It is also the precursor of some characteristic aroma volatiles in both fruits playing, thus, an important visual and olfactory impact in consumer choice. While sharing the same main pigment, tomato and watermelon fruits show substantial biochemical and physiological differences during ripening. Tomato is climacteric while watermelon is non-climacteric; unripe tomato fruit is green, mainly contributed by chlorophylls and xanthophylls, while young watermelon fruit mesocarp is white and contains only traces of carotenoids. Various studies comparatively evaluated in vivo pigment development in ripening tomato and watermelon fruits. However, in most cases, other classes of compounds have not been considered. We believe this knowledge is fundamental for targeted breeding aimed at improving the functional quality of elite cultivars. Hence, in this paper, we critically review the recent understanding underlying the biosynthesis, accumulation and regulation of different bioactive compounds (carotenoids, phenolics, aroma volatiles, and vitamin C) during tomato and watermelon fruit ripening. We also highlight some concerns about possible harmful effects of excessive uptake of bioactive compound on human health. We found that a complex interweaving of anabolic, catabolic and recycling reactions, finely regulated at multiple levels and with temporal and spatial precision, ensures a certain homeostasis in the concentrations of carotenoids, phenolics, aroma volatiles and Vitamin C within the fruit tissues. Nevertheless, several exogenous factors including light and temperature conditions, pathogen attack, as well as pre- and post-harvest manipulations can drive their amounts far away from homeostasis. These adaptive responses allow crops to better cope with abiotic and biotic stresses but may severely affect the supposed functional quality of fruits.